2020
DOI: 10.5812/ijp.95784
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Celox® Powder on Initial Hemostasis After Cardiac Catheterization in Pediatric Patients with Congenital Heart Disease: A Prospective Study

Abstract: Background: Ordinary pressure dressing for hemostasis after cardiac catheterization is time consuming and might cause some problems, such as pain or loss of blood, which has to be controlled, particularly in pediatric patient. Using Celox® (chitosan) powder dressing might cause quicker initial hemostasis. Methods: In this prospective study, we assessed Celox® powder among patients in hospitals affiliated with Shiraz University of Medical Sciences, from November 2017 to February 2018. The patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Time to hemostasis at the arterial puncture site: Review of the results of the five studies showed that Arbel et al [Arbel 2011] and Nguyen et al [Nguyen 2007] measured the continuous time to hemostasis at the arterial puncture sites and found that the time to hemostasis in the EG was significantly shorter than in the CG (mean=5.6±2.1, P < 0.001, ChitoSeal=16.2±4.9, CloSurPAD=16.0±5.3, P = 0.005). However, in a study by Amoozgar et al [Amoozgar 2020], there was no significant difference in the time to arterial hemostasis between the two groups (EG:17.2, CG:20.3, P = 0.77). Other studies classified the time to hemostasis as categorical data.…”
Section: Review Of Literature Screening Results and Research Results In Each Articlementioning
confidence: 86%
See 3 more Smart Citations
“…Time to hemostasis at the arterial puncture site: Review of the results of the five studies showed that Arbel et al [Arbel 2011] and Nguyen et al [Nguyen 2007] measured the continuous time to hemostasis at the arterial puncture sites and found that the time to hemostasis in the EG was significantly shorter than in the CG (mean=5.6±2.1, P < 0.001, ChitoSeal=16.2±4.9, CloSurPAD=16.0±5.3, P = 0.005). However, in a study by Amoozgar et al [Amoozgar 2020], there was no significant difference in the time to arterial hemostasis between the two groups (EG:17.2, CG:20.3, P = 0.77). Other studies classified the time to hemostasis as categorical data.…”
Section: Review Of Literature Screening Results and Research Results In Each Articlementioning
confidence: 86%
“…Arbel et al [Arbel 2011], Nguyen et al [Nguyen 2007], and Amoozgar et al [Amoozgar 2020] collected continuous The Heart Surgery Forum #2021-3997 E838 data on the time to hemostasis at arterial puncture sites, and according to our meta-analysis, the heterogeneity between the studies was high (I 2 = 52%). The overall effect showed that the diamond was biased toward the EG with added chitin hemostatic patches, indicating that the time to hemostasis at arterial puncture sites was significantly reduced (Std.…”
Section: Overall Effect Of Adding Chitin Hemostatic Patch On Time To Hemostasismentioning
confidence: 81%
See 2 more Smart Citations
“…Everyday practice often overlooks or underdiagnoses anaemia in children with congenital heart disease (CHD), particularly in cyanotic youngsters who exhibit elevated haematocrit values as a result of persistent hypoxia. 12,13 The present study is thus conducted to find out the prevalence of iron deficiency anaemia in children less than 15 years with congenital heart disease at a tertiary care centre and compare them with cases without congenital heart disease.…”
Section: Introductionmentioning
confidence: 99%